ANALISIS KEMAMPUAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 - Vidiarti, Erni; Zulhaini, Zulhaini; Andrizal, Andrizal (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
This research aims to analyze the ability of Islamic religious education teachers in the preparation of the plan of implementation of the learning (RPP) Curriculum 2013 in SD Negeri 016 Source Flat Singingi Subdistrict. This research includes research with qualitative, descriptive approach to research that is used to describe and analyze the phenomena, events, social activities, attitudes, beliefs, perceptions, and people individually and the group, with the techniques of data collection through the techniques of observation, interview and documentation. Results of the study showed that the ability of guru PAI in the preparation of RPP 2013 in elementary curriculum Land Resource 016 Flat Sub Singingi categorized "very good" with four stages of the observation by the author with the average scores 86.25% ketercapaian the ability of teachers, it is visible from the completeness of the RPP made by the teacher concerned.Keywords: Ability of PAI Teachers; RPP; Curriculum 2013.